MBRS-20. CSF-DERIVED CIRCULATING TUMOR DNA AS A BIOMARKER FOR DISEASE PROGRESSION AND TUMOR EVOLUTION IN MEDULLOBLASTOMA. (4th December 2020) - Liu, Anthony Pak-Yin; Kumar, Rahul; Kyle, Smith; Paul, Leena; Chintagumpala, Murali; Bouffet, Eric; Fisher, Michael J; Hassall, Tim; Gururangan, Sri; Hansford, Jordan; Cohn, Richard; Ellison, David W; et al.
Abstract: BACKGROUND: Cell-free DNA (cfDNA) profiling has been shown to carry utility as a clinically relevant biomarker in a variety of cancers, but studies in pediatric brain tumors, including medulloblastoma, are scarce. We hereby evaluated the actionability of profiling cfDNA from cerebrospinal fluid (CSF) based on a multi-institutional cohort of children with medulloblastoma. METHODS: 103 children aged ≥ 3 years with medulloblastoma harboring chromosomal aneuploidy enrolled on two prospective therapeutic trials were included. cfDNA was extracted from CSF obtained longitudinally, and profiled by low-coverage whole-genome sequencing (lcWGS) for annotating copy-number variants (CNVs). cfDNA-derived CNVs were compared against patient-matched primary tumor-derived CNVs and correlated with outcome. cfDNA profiles at diagnosis and relapse were compared to evaluate tumor evolution. RESULTS: Tumor-derived somatic CNVs were detected in 72% of baseline cfDNA samples, with higher detection rate in samples from patients with metastatic disease than those without (90% versus 50%, chi-square p=0.001). Longitudinal profiling of cfDNA revealed correlation between CNV detectability and clinical course, with detection of tumor-derived CNVs in cfDNA samples predating radiographic progression for ≥ 3 months in 62% of relapsing patients. Presence of cfDNA-derived CNVs in CSF collected during chemotherapy and at the end of therapy was significantly associated with inferior PFS (log-rank p<0.0001 for both time-points). Comparison of CNV profiles from cfDNA at baseline and relapse revealed molecular divergence in a subset of patients. CONCLUSION: These results carry major implications and supports the incorporation of cfDNA profiling in upcoming medulloblastoma protocols for more sensitive and accurate disease monitoring and personalization of treatment.